Analisis Hukum Keabsahan Pernikahan di Bawah Umur Pasca Revisi UU Perkawinan - Muhamad Ari Kristiono; Aturkian Laia (INDO PUBLISHING, 2026)
The legal reform through Law Number 16 of 2019 raising the marriage age limit to 19 years aims to strengthen child protection, but the marriage dispensation provision in Article 7 paragraph (2) actually creates ambiguity and normative contradiction. This research examines the legality of underage marriage after the revision of the Marriage Law with a focus on normative regulation, dispensation implementation, and its alignment with child protection principles. Using a descriptive-analytical normative legal approach, this research examines laws and regulations, court decisions, and related academic literature. The findings indicate that although the regulation establishes a uniform age limit, the dispensation mechanism creates a paradoxical dualism where the state commits to protecting children yet still opens space for legitimizing child marriage through judicial channels. A significant surge in dispensation applications occurred, with judges considering urgent reasons such as pregnancy out of wedlock, cultural pressure, economic conditions, and the principle of maslahah. The dispensation provision is not synchronized with the Child Protection Law, placing judges in a dilemmatic position between emergency reasons and the best interests of the child. The research concludes that underage marriage remains valid through the dispensation route, but this policy has not been effective in reducing child marriage rates. Regulatory revision, procedural improvement, enhanced supervision, and regulatory harmonization are needed to achieve legal certainty and optimal child protection.